ZCTs knockdown using antisense LNA GapmeR in specialized photomixotrophic cell suspensions of Catharanthus roseus: Rerouting the flux towards mono and dimeric indole alkaloids - Verma, Priyanka; Khan, Shamshad Ahmad; Parasharami, Varsha; Mathur, Ajay Kumar (Physiology and Molecular Biology of Plants, 2021)
The present study was carried out to silence the transcription factor genes ZCT1, ZCT2 and ZCT3 via lipofectamine based antisense LNA GapmeRs transfection into the protoplasts of established photomixotrophic cell suspensions. The photomixotrophic cell suspensions with a threshold of 0.5% sucrose were raised and established using two-tiered CO2 providing flasks kept under high light intensity. The photomixotrophic cell suspensions showed morphologically different thick-walled cells under scanning electron microscopic analysis in comparison to the simple thin-walled parenchymatous control cell suspensions. The LC-MS analysis registered the vindoline production (0.0004 +/- 0.0001 mg/g dry wt.) in photomixotrophic cell suspensions which was found to be absent in control cell suspensions. The protoplasts were isolated from the photomixotrophic cell suspensions and subjected to antisense LNA GapmeRs silencing. Three lines, viz. Z1A, Z2C and Z3G were obtained where complete silencing of ZCT1, ZCT2 and ZCT3 genes, respectively, was observed. The Z3G line was found to show maximum production of vindoline (0.038 +/- 0.001 mg/g dry wt.), catharanthine (0.165 +/- 0.008 mg/g dry wt.) and vinblastine (0.0036 +/- 0.0003 mg/g dry wt.). This was supported by the multifold increment in the gene expression of TDC, SLS, STR, SGD, d4h, dat, CrT16H and Crprx. The present work indicates the master regulation of ZCT3 knockdown among all three ZCTs transcription factors in C. roseus to enhance the terpenoid indole alkaloids production. The successful silencing of transcription repressor genes has been achieved in C. roseus plant system by using photomixotrophic cell cultures through GapmeR based silencing. The present study is a step towards metabolic engineering of the TIAs pathway using protoplast transformation in C. roseus.
Keywords: Catharanthine; LC-MS; Protoplast; TIAs; Vinblastine; Vindoline